The Construction of the (Convincing) Child Subject in Victorian Literature (Groundings Undergraduate, 2015)
Drawing on genre theory and especially Shklovsky’s definition of ostranenie, or defamiliarisation, this article investigates the evolution of the construction and understanding of the child subject in Victorian literature. Engaging not only with the role of literature in shaping representations of the child, but also how the child's knowledge is furthered or tested through the genre of ‘children’s literature’, this article offers close readings of several key novels. From the ‘plastic children’ of Dickens to Carroll’s empowered Alice, this article fuses a discussion of the technique of defamiliarisation in creating a convincing child voice with an emphasis on the implications of doing so. Moreover, it traces the roots of the contemporary child’s agency as well as the linguistic formulations of childhood, language, and civil society. In weighing the distinctions between nineteenth-century realism and non-sense, this article ultimately proposes that the ostranenie synonymous with the technique of the child’s standpoint evokes a coded social commentary, shifting the child from an affective to a political narrative device.
Keywords: Child Subject; Character; Construction; Victorian; Literature; Representation; Voice; Convincing; Agency